2016
DOI: 10.1182/blood-2016-03-706317
|View full text |Cite
|
Sign up to set email alerts
|

Specific combinations of donor and recipient KIR-HLA genotypes predict for large differences in outcome after cord blood transplantation

Abstract: Key Points• Patients homozygous for HLA-C2 group alleles have worse outcomes after CBT.• CB selection based on the combination of NK licensing and activating KIRs may improve outcomes after CBT.The ability of cord blood transplantation (CBT) to prevent relapse depends partly on donor natural killer (NK) cell alloreactivity. NK effector function depends on specific killer-cell immunoglobulin-like receptors (KIR) and HLA interactions. Thus, it is important to identify optimal combinations of KIR-HLA genotypes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 41 publications
2
48
0
Order By: Relevance
“…Empirical data on the NK cell education process following transplantation remain controversial. In the setting of CBT, Sekine et al (2016) reported that HLA-C1/x patients should receive an HLA-C1-KIR2DL2/L3/S2 cord blood graft, while HLA-C2/C2 patients may benefit from an HLA-C2-KIR2DL1/S1 graft. However, Sungur et al (2013) have indicated that NK cell licensing corresponds with the donor and not the host MHC haplotype following mismatched allo-HSCT in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Empirical data on the NK cell education process following transplantation remain controversial. In the setting of CBT, Sekine et al (2016) reported that HLA-C1/x patients should receive an HLA-C1-KIR2DL2/L3/S2 cord blood graft, while HLA-C2/C2 patients may benefit from an HLA-C2-KIR2DL1/S1 graft. However, Sungur et al (2013) have indicated that NK cell licensing corresponds with the donor and not the host MHC haplotype following mismatched allo-HSCT in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with at least one C1 epitope transplanted from cord blood with C1 and KIR2DL2/L3/S2 had earlier recovery of licensed NK cells and less relapses. 46 The different observations in different studies is explained by differences in regimen intensities, donor type and HLA-matching, stem cell source, T-cell content of the graft as well as stem cell and NK cell content. Most studies used myeloablative conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Sekine et al (39) reported that only patients homozygous for HLA-C2 group alleles had a higher 1-year relapse rate and worse survival after UCBT than did HLA-C1/C1 or HLA-C1/C2 patients. Unlike our work, two UCB units were used in almost all the patients of this study and they use the dominant engrafting unit of the two to determine the KIR-ligand compatibility.…”
Section: Discussionmentioning
confidence: 99%